Vox clamantis in deserto: a survey among Italian psychiatrists on defensive medicine and professional liability - Scognamiglio, Pasquale; Morena, Donato; Di Fazio, Nicola; Delogu, Giuseppe; Iniziato, Valeria; La Pia, Silvestro; Saviano, Pasquale; Frati, Paola; Fineschi, Vittorio (Frontiers in Psychiatry, 2023)
Professional liability for psychiatrists in Italy is currently a matter of lively debate. Specifically, overwhelming pressure on psychiatrists’ duties has been brought by regulatory developments, such as the closure of forensic psychiatric hospitals, with the consequent return of offenders to community-based care, and the mental health consequences of the pandemic. According to Italian courts, psychiatrists are not only responsible for diagnostic and therapeutic appropriateness but also for the effects of their interventions on patients, and their behaviors. The aim of this study was to explore the attitude and behaviors of Italian psychiatrists regarding defensive medicine and professional liability. A total sample of 254 psychiatrists was surveyed by means of a quantitative online questionnaire. Most psychiatrists reported practicing defensive medicine (n. 153/254, % 60,2) and felt that their position of guarantee compromised their work in healthcare for patients (n. 138/253, % 54,3). Age correlated inversely with acknowledgment of defensive practices (r=-0.245, p<0.001), with younger physicians more prone to defensive medicine (p=0.013), particularly for patients at risk of suicide or violence. Psychiatrists in ‘closed’ settings (hospital wards, residential and rehabilitation centers, mental health service units in prison) reported more malpractice claims (p=0.037) and complaints (p=0.031), as well as a greater propensity to act defensively. In the treatment of patients with violent behavior, suicidal ideation, dual diagnoses, and criminal convictions, defensive practices were associated more with perceived legal risks (r=0.306, p<0.001) than actual legal involvement (p>0.05). Anxiety, anger, and restlessness were common reactions to legal complaints, involving n. 50/254 (% 19,7) respondents, with 40% reporting impaired functioning. Most psychiatrists (n. 175/253, % 68,9) were concerned about both civil and criminal laws regarding their professional responsibility, but many were not fully informed about recent legislative regulations and younger physicians resulted scarcely trained in risk management (p<0.001). In conclusion, our findings suggest that defensive medicine is a common phenomenon among psychiatrists and their position of guarantee drives this attitude. Education on legal implications and risk management should be provided starting from the university and continuing over time, to improve the knowledge of young and senior doctors on professional liability and inform their decision-making processes.